Inference of Internal Stress in a Cell Monolayer - Nier, Vincent; Jain, Shreyansh; Lim, Chwee Teck; Ishihara, Shuji; Ladoux, Benoît; Marcq, Philippe (Biophysical Journal, 2016)
We combine traction force data with Bayesian inversion to obtain an absolute estimate of the internal stress field of a cell monolayer. The method, Bayesian inversion stress microscopy, is validated using numerical simulations performed in a wide range of conditions. It is robust to changes in each ingredient of the underlying statistical model. Importantly, its accuracy does not depend on the rheology of the tissue. We apply Bayesian inversion stress microscopy to experimental traction force data measured in a narrow ring of cohesive epithelial cells, and check that the inferred stress field coincides with that obtained by direct spatial integration of the traction force data in this quasi one-dimensional geometry.
CRIS-Team Scopus Importer:2024-02-19